2013
DOI: 10.21425/f55113391
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale biogeography: tidal elevation strongly affects population genetic structure and demographic history in intertidal fishes

Abstract: Numerous studies have demonstrated population genetic structuring in marine species, yet few have investigated the effect of vertical zonation on gene flow and population structure. Here we use three sympatric, closely related clinid species, Clinus cottoides, C. superciliosus and Muraenoclinus dorsalis, to test whether zonation on South African intertidal rocky shores affects phylogeographic patterns. We show that the high-shore restricted species has reduced gene flow and considerably higher F ST values (F S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…1). Such reduced gene flow was also shown for rocky shore fishes [22], [26] and an endemic sea urchin, Parechinus angulosus [24] strongly suggesting that gene flow is reduced for inshore coastal species in this region. Cape Point is also characterized as a region where a major biogeographic break occurs [19].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…1). Such reduced gene flow was also shown for rocky shore fishes [22], [26] and an endemic sea urchin, Parechinus angulosus [24] strongly suggesting that gene flow is reduced for inshore coastal species in this region. Cape Point is also characterized as a region where a major biogeographic break occurs [19].…”
Section: Discussionmentioning
confidence: 60%
“…Such variance in patterns also applies to the study of demographic change; some marine species have been shown to maintain demographically stable populations throughout the LGM, without significant changes in population sizes, while others show population bottlenecks with post-LGM recolonization; both scenarios seem equally plausible [8] and can be found even in closely related species [26]. To better understand the evolutionary processes that drive changes in population sizes and distributions, it is important to carefully consider the timing of population expansions and contractions [27].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar Pleistocene population expansion estimates have been reported for other South African coastal organisms, including the Cape sea urchin Parechinus angulosus [32], the clinid species Clinus cottoides , C . superciliosus and Muraenoclinus dorsalis [37], and the southern African barnacle Tetraclita serrata [41]. …”
Section: Discussionmentioning
confidence: 99%
“…At least three marine biogeographic provinces are recognised; the cool-temperate Namaqua province on the western coastline (Lüderitz, Namibia to Cape Point, South Africa), the warm-temperate Agulhas province on the southern coastline (Cape Point to Algoa Bay, South Africa) and the sub-tropical East Coast Province on the eastern side (Algoa Bay to the northern borders of the Kwazulu Natal coastline) [36], see Fig 1. The exact spatial boundaries between these provinces are not strictly delineated, as barriers vary across taxa and there are few congruent patterns [2], [32], even with closely related species [37], which forms transition zones. For estuarine organisms an additional barrier to dispersal is presented by South Africa’s highly dynamic estuarine system, whereby approximately 70% of all estuaries are either permanently disconnected from the sea by the formation of sand bars at the mouth (closed estuaries) or are only temporarily open [38].…”
Section: Introductionmentioning
confidence: 99%